The impact of surgical experience and frequency of practice on perioperative outcomes in pancreatic surgery - Krautz, Christian; Haase, Elisabeth; Elshafei, Moustafa; Saeger, Hans Detlev; Distler, Marius; Grützmann, Robert; Weber, Georg (BMC Surgery, 2019)
Objective: We aimed to determine the impact of surgical experience and frequency of practice on perioperative morbidity and mortality in pancreatic surgery. Methods: 1281 patients that underwent pancreatic resections from 1993 to 2013 were retrospectively analyzed using logistic regression models. All cases were stratified according to the surgeon's level of experience, which was based on the number of previously performed pancreatic resections and the extent of received supervision (novice: N < 20/intensive; intermediate: N = 21-90/decreasing; and experienced surgeon: N > 90/none). Additional stratification was based on the frequency of practice (sporadic: 3 resections > 6 weeks, frequent: 3 resections ≤6 weeks). Results: The novice and experienced categories were related to a decreased risk of postoperative pancreatic fistulas (odds ratio [OR] 0.46, 95% confidence interval [CI] 0.26-0.82 and 0.54, 95% CI 0.36-0.82) and in-hospital mortality (OR 0.45, 95% CI 0.17-1.16 and 0.42, 95% CI 0.21-0.83) compared to the intermediate category. Frequent practice was associated with a significantly lower risk of delayed gastric emptying (OR 0.56, 95% CI 0.38-0.83), postpancreatectomy hemorrhage (OR 0.64, 95% CI 0.42-0.98) and in-hospital mortality (OR 0.45, 95% CI 0.24-0.87). Conclusions: Our results emphasize the importance of supervision within a pancreatic surgery training program. In addition, our data underline the need of a sufficient patient caseload to ensure frequent practice.
CRIS-Team Scopus Importer:2019-08-27
Keywords: Frequency of practice; In-hospital mortality; Pancreatic surgery; Perioperative outcomes; Surgical experience; Volume-outcome relationship